Optomechanical Probes with Tailored Material and Shape Asymmetry Assembled Using DNA Origami - Ruiz-Arce, DD; Benešová, Markéta; Protiva, Václav; Kočišek, Jaroslav; Pilát, Zdeněk; Ježek, Jan; Silhan, Lukas; Zemánek, Pavel; Jonas, Alexandr; Sala, Leo (Nano Letters, 2026)
Keywords: AIF; BF; LF; MF

Nanomechanical state amplifier based on optical inverted pendulum - Duchaň, Martin; Šiler, Martin; Jákl, Petr; Brzobohatý, Oto; Rakhubovsky, Andrey; Filip, Radim; Zemánek, Pavel (Communications Physics, 2025)
Keywords: LF; MF

Preparation and pilot experiments on microfluidic chip with surface acoustic waves - J. Vejrosta; S. Cabalová; T. Plichta; M. Šerý; T. Maňka; O. Samek; P. Zemánek (23rd Slovak-Czech-Polish Optical Conference on Wave and Quantum Aspects of Contemporary Optics, 2025)
Keywords: AIF; MF

PT-like phase transition and limit cycle oscillations in non-reciprocally coupled optomechanical oscillators levitated in vacuum - Liška, Vojtěch; Zemánková, Tereza; Jákl, Petr; Šiler, Martin; Simpson, Stephen H.; Zemánek, Pavel; Brzobohatý, Oto (Nat. Phys., 2024)
Nanoparticles levitated in an optical trap provide a versatile platform to study mechanical oscillators in a controlled environment with tuneable parameters. Recently, it has become possible to couple two of these optomechanical oscillators. Here we demonstrate the collective non-Hermitian dynamics of such a pair of non-conservatively coupled oscillators. We take advantage of the tunability of the optical interactions between the particles in our system and set the optical interaction between the particles to be purely non-reciprocal. By continuously varying the relative power of the trapping beams, we take the system through a transition similar to a parity–time phase transition. A Hopf bifurcation at a critical point results in the formation of collective limit cycle oscillations, resembling those observed in phonon lasers. These coupled levitated oscillators provide a platform for exceptional point optomechanical sensing and can be extended to multi-particle systems, paving the way for the development of topological optomechanical media.
Keywords: LF; MF

SERS-Tags: Selective Immobilization and Detection of Bacteria by Strain-Specific Antibodies and Surface-Enhanced Raman Scattering - Benešová, Markéta; Bernatová, Silvie; Mika, Filip; Pokorná, Zuzana; Ježek, Jan; Šiler, Martin; Samek, Ota; Růžička, Filip; Rebrošová, Katarína; Zemánek, Pavel; Pilát, Zdeněk (Biosensors, 2023)
Keywords: BF; MF

Synchronization of spin-driven limit cycle oscillators optically levitated in vacuum - Brzobohatý, Oto; Duchaň, Martin; Jákl, Petr; Ježek, Jan; Šiler, Martin; Zemánek, Pavel; Simpson, Stephen H. (Nature Communications, 2023)
Keywords: LF; MF

All-optical sub-Kelvin sympathetic cooling of a levitated microsphere in vacuum - Y. Arita; G. D. Bruce; E. M. Wright; S. H. Simpson; P. Zemánek; K. Dholakia (Optica, 2022)
We demonstrate all-optical sympathetic cooling of a laser-trapped microsphere to sub-Kelvin temperatures, mediated by optical binding to a feedback-cooled adjacent particle. Our study opens prospects for multi-particle quantum entanglement and sensing in levitated optomechanics.
Keywords: LF; MF

Challenges on optical printing of colloidal nanoparticles - Violi, Ianina L.; Martinez, Luciana P.; Barella, Mariano; Zaza, Cecilia; Chvátal, Lukas; Zemánek, Pavel; Gutierrez, Marina V.; Paredes, Maria Y.; Scarpettini, Alberto F.; Olmos-Trigo, Jorge; Pais, Valeria R.; Noblega, Ivan Diaz; et al. (J. Chem. Phys., 2022)
Keywords: LF; MF

Endoscopic Imaging Using a Multimode Optical Fibre Calibrated with Multiple Internal References - Jákl, Petr; Šiler, Martin; Ježek, Jan; Cifuentes, Angel; Trägårdh, Johanna; Zemánek, Pavel; Cizmar, Tomas (Photonics, 2022)
Keywords: BF; KF; MF

In Vivo Contrast Imaging of Rat Heart with Carbon Dioxide Foam - Karalko, Anton; Kesa, Peter; Jelinek, Frantisek; Sefc, Ludek; Ježek, Jan; Zemánek, Pavel; Grus, Tomas (SENSORS, 2022)
Keywords: BF; MF

Optically transportable optofluidic microlasers with liquid crystal cavities tuned by the electric field - Jonas, Alexandr; Pilát, Zdeněk; Ježek, Jan; Bernatová, Silvie; Jedlička, Petr; Aas, Mehdi; Kiraz, Alper; Zemánek, Pavel (ACS Applied Materials & Interfaces, 2021)
Keywords: BF; LF; MF

Raman Microspectroscopic Analysis of Selenium Bioaccumulation by Green Alga Chlorella vulgaris - Kizovský, Martin; Pilát, Zdeněk; Mylenko, Mykola; Hrouzek, Pavel; Kuta, Jan; Skoupý, Radim; Krzyžánek, Vladislav; Hrubanová, Kamila; Adamczyk, Olga; Ježek, Jan; Bernatová, Silvie; Klementová, Tereza; et al. (Biosensors, 2021)
Keywords: BF; MF

Stochastic Hopf bifurcations in vacuum optical tweezers - Simpson, Stephen H.; Arita, Yoshihiko; Dholakia, Kishan; Zemánek, Pavel (Phys. Rev. A, 2021)
Keywords: LF; MF

Using the transient trajectories of an optically levitated nanoparticle to characterize a stochastic Duffing oscillator - Flajšmanová, Jana; Šiler, Martin; Jedlička, Petr; Hrubý, František; Brzobohatý, Oto; Filip, Radim; Zemánek, Pavel (Scientific Reports, 2020)
Keywords: LF; MF

Identification of ability to form biofilm in Candida parapsilosis and Staphylococcus epidermidis by Raman spectroscopy - Rebrošová, Katarína; Šiler, Martin; Samek, Ota; Růžička, Filip; Bernatová, Silvie; Ježek, Jan; Zemánek, Pavel; Holá, Veronika (Future Microbiology, 2019)
Aim: Finding rapid, reliable diagnostic methods is a big challenge in clinical microbiology. Raman spectroscopy is an optical method used for multiple applications in scientific fields including microbiology. This work reports its potential in identifying biofilm positive strains of Candida parapsilosis and Staphylococcus epidermidis. Materials & methods: We tested 54 S. epidermidis strains (23 biofilm positive, 31 negative) and 51 C. parapsilosis strains (27 biofilm positive, 24 negative) from colonies on Mueller-Hinton agar plates, using Raman spectroscopy. Results: The accuracy was 98.9% for C. parapsilosis and 96.1% for S. epidermidis. Conclusion: The method showed great potential for identifying biofilm positive bacterial and yeast strains. We suggest that Raman spectroscopy might become a useful aid in clinical diagnostics.
Keywords: BF; KF; MF

Optical Trapping, Optical Binding, and Rotational Dynamics of Silicon Nanowires in Counter-Propagating Beams - Donato, Maria G.; Oto Brzobohatý; S. H. Simpson; Irrera, Alessia; Leonardi, Antonio A.; Lo Faro, Maria J.; Vojtech Svak; Maragò, Onofrio M.; P. Zemánek (Nano Lett., 2019)
Keywords: LF; MF

Optomechanical properties of optically self-arranged colloidal waveguides - Oto Brzobohatý; Lukáš Chvátal; P. Zemánek (Opt. Lett., 2019)
Keywords: LF; MF

Spin to orbital light momentum conversion visualized by particle trajectory - Alejandro V. Arzola; Lukáš Chvátal; P Jákl; P. Zemánek (Sci. Rep., 2019)
Keywords: LF; MF

Tunable Soft-Matter Optofluidic Waveguides Assembled by Light - Oto Brzobohatý; Lukáš Chvátal; A. Jonáš; M Šiler; J. Kaňka; J Ježek; P. Zemánek (ACS Phot., 2019)
Keywords: LF; MF

Wavelength-Dependent Optical Force Aggregation of Gold Nanorods for SERS in a Microfluidic Chip - Bernatová, Silvie; Donato, Maria Grazia; Ježek, Jan; Pilát, Z.; Samek, Ota; Magazzu, Alessandro; Maragò, Onofrio M.; Zemánek, Pavel; Gucciardi, Pietro G. (J. Phys. Chem. C, 2019)
Keywords: BF; MF

Detection of chloroalkanes by surface-enhanced raman spectroscopy in microfluidic chips - Z. Pilát; Kizovský, M.; J Ježek; Krátký, S.; Sobota, J.; M Šiler; O. Samek; Buryška, T.; Vaňáček, P.; Damborský, J.; Prokop, Z.; P. Zemánek (Sensors, 2018)
Keywords: BF; MF

Diffusing up the Hill: Dynamics and Equipartition in Highly Unstable Systems - M Šiler; Ornigotti, L.; Oto Brzobohatý; P Jákl; Artem Ryabov; Holubec, V.; P. Zemánek; Radim Filip (Phys. Rev. Lett., 2018)
Keywords: LF; MF

Enhancement of the `tractor-beam' pulling force on an optically bound structure - Damková, Jana; Lukáš Chvátal; J Ježek; Oulehla, Jindrich; Oto Brzobohatý; P. Zemánek (Light: Sci. Appl., 2018)
Keywords: LF; MF

Microfluidic Cultivation and Laser Tweezers Raman Spectroscopy of E-coli under Antibiotic Stress - Z. Pilát; Silva Bernatová; J Ježek; Kirchhoff, J.; Tannert, A.; Neugebauer, U.; O. Samek; P. Zemánek (Sensors, 2018)
Keywords: BF; MF

Transverse spin forces and non-equilibrium particle dynamics in a circularly polarized vacuum optical trap - Vojtech Svak; Oto Brzobohatý; M Šiler; P Jákl; J. Kaňka; P. Zemánek; S. H. Simpson (Nature Commun., 2018)
Keywords: LF; MF

Accuracy and Mechanistic Details of Optical Printing of Single Au and Ag Nanoparticles - Gargiulo, Juliàn; Violi, Ianina L; Cerrota, Santiago; Lukáš Chvátal; Cortès, Emiliano; Perassi, Eduardo M; Diaz, Fernando; P. Zemánek; Stefani, Fernando D (ACS nano, 2017)
Keywords: LF; MF

Differentiation between Staphylococcus aureus and Staphylococcus epidermidis strains using Raman spectroscopy - K. Rebrošová; M Šiler; O. Samek; F. Růžička; Silva Bernatová; J Ježek; P. Zemánek; V. Holá (Future Microbiology, 2017)
Keywords: BF; MF

Dynamics of an optically bound structure made of particles of unequal sizes - Vítězslav Karásek; M Šiler; Oto Brzobohatý; P. Zemánek (Opt. Lett., 2017)
Keywords: LF; MF

Effects of Infrared Optical Trapping on Saccharomyces cerevisiae in a Microfluidic System - Z. Pilát; A. Jonáš; J Ježek; P. Zemánek (Sensors, 2017)
Keywords: BF; MF

Morphological and Production Changes in Planktonic and Biofilm Cells Monitored Using SEM and Raman Spectroscopy - K. Hrubanová; V. Krzyžánek; O. Samek; R. Skoupý; M Šiler; J Ježek; S. Obruča; P. Zemánek (Microscopy and Microanalysis, 2017)
Keywords: BF; MF

Omnidirectional Transport in Fully Reconfigurable Two Dimensional Optical Ratchets - Alejandro V. Arzola; Villasante-Barahona, Mario; Karen Volke-Sepúlveda; P Jákl; P. Zemánek (Phys. Rev. Lett., 2017)
Keywords: LF; MF

Optical Binding of Nanowires - S. H. Simpson; P. Zemánek; Maragò, Onofrio M.; Jones, Philip H.; Hanna, Simon (Nano Lett., 2017)
Keywords: LF; MF

Rapid identification of staphylococci by Raman spectroscopy - K. Rebrošová; M Šiler; O. Samek; F. Růžička; S. Bernatová; V. Holá; J Ježek; P. Zemánek; J. Sokolová; P. Petráš (Sci. Rep., 2017)
Keywords: BF; MF

Thermal tuning of spectral emission from optically trapped liquid-crystal droplet resonators - A. Jonáš; Z. Pilát; J Ježek; Silva Bernatová; T. Fořt; P. Zemánek; Mehdi Aas; Alper Kiraz (J. Opt. Soc. Am. B, 2017)
Keywords: BF; MF

Thermally induced micro-motion by inflection in optical potential - M Šiler; P Jákl; Oto Brzobohatý; Artem Ryabov; Radim Filip; P. Zemánek (Sci. Rep., 2017)
Keywords: LF; MF

Chiral particles in the dual-beam optical trap - Oto Brzobohatý; Hernandez, Raul Josue; S. H. Simpson; Mazzulla, Alfredo; Cipparrone, Gabriella; P. Zemánek (Opt. Express, 2016)
Keywords: MF

Direct measurement of the temperature profile close to an optically trapped absorbing particle - M Šiler; J Ježek; P Jákl; Z. Pilát; P. Zemánek (Opt. Lett., 2016)
Keywords: MF

Holographic Raman tweezers controlled by Multimodal Natural User Interface - Z. Tomori; P. Keša; M. Nikorovič; J. Kaňka; P Jákl; M. Šerý; Silva Bernatová; E. Valušová; M. Antalík; P. Zemánek (J. Opt., 2016)
Keywords: MF

Morphological and Production Changes in Stressed Red Yeasts Monitored Using SEM and Raman Spectroscopy - K. Hrubanová; O. Samek; A. Haroniková; Silva Bernatová; P. Zemánek; I. Márová; V. Krzyžánek (Microscopy and Microanalysis, 2016)
Keywords: MF

Noise-to-signal transition of a Brownian particle in the cubic potential: I. general theory - Radim Filip; P. Zemánek (Journal of Optics, 2016)
Keywords: MF

Noise-to-signal transition of a Brownian particle in the cubic potential: II. optical trapping geometry - P. Zemánek; M Šiler; Oto Brzobohatý; P Jákl; Radim Filip (Journal of Optics, 2016)
Keywords: MF

Quantitative Raman Spectroscopy Analysis of Polyhydroxyalkanoates Produced by Cupriavidus necator H16 - O. Samek; S. Obruča; M Šiler; P. Sedláček; Pavla Benešová; D. Kučera; I. Márová; J Ježek; Silva Bernatová; P. Zemánek (Sensors, 2016)
Keywords: MF

Synchronization of colloidal rotors through angular optical binding - S. H. Simpson; Lukáš Chvátal; P. Zemánek (Phys. Rev. A, 2016)
Keywords: MF

Thermally-induced passage and current of particles in highly unstable optical potential - Artem Ryabov; P. Zemánek; Radim Filip (Phys. Rev.E, 2016)
Keywords: MF

Binding of a pair of Au nanoparticles in a wide Gaussian standing wave - Lukáš Chvátal; Oto Brzobohatý; P. Zemánek (Opt. Rev., 2015)
Keywords: MF

Complex rotational dynamics of multiple spheroidal particles in a circularly polarized, dual beam trap - Oto Brzobohatý; Alejandro V. Arzola; M Šiler; Lukáš Chvátal; P Jákl; S. H. Simpson; P. Zemánek (Opt. Express, 2015)
Keywords: MF

Cryo-SEM and Raman Spectroscopy Study of the Involvement of Polyhydroxyalkanoates in Stress Response of Bacteria - V. Krzyžánek; K. Hrubanová; O. Samek; S. Obruča; I. Márová; Silva Bernatová; M Šiler; P. Zemánek (Microscopy and Microanalysis, 2015)
Keywords: MF

Identification of individual biofilm-forming bacterial cells using Raman tweezers - O. Samek; Silva Bernatová; J Ježek; M Šiler; M. Šerý; V. Krzyžánek; K. Hrubanová; P. Zemánek; V. Holá; F. Růžička (J. Biomed. Opt., 2015)
Keywords: MF

Influence of Culture Media on Microbial Fingerprints Using Raman Spectroscopy - K. Mlynariková; O. Samek; Silva Bernatová; F. Růžička; J Ježek; A. Haroniková; M Šiler; P. Zemánek; V. Holá (Sensors, 2015)
Keywords: MF

Monitoring of Multilayered Bacterial Biofilm Morphology by Cryo-SEM for Raman Spectroscopy Measurements - K. Hrubanová; Silva Bernatová; O. Samek; M. Šerý; P. Zemánek; J. Nebesářová; F. Růžička; V. Krzyžánek (Microscopy and Microanalysis, 2015)
Keywords: MF

Non-spherical gold nanoparticles trapped in optical tweezers: shape matters - Oto Brzobohatý; M Šiler; J. Trojek; Lukáš Chvátal; Vítězslav Karásek; P. Zemánek (Opt. Express, 2015)
Keywords: MF

Optical trapping in secondary maxima of focused laser beam - M Šiler; P. Zemánek (J. Quant. Spectrosc. Radiat. Transf., 2015)
Keywords: MF

SEM and Raman Spectroscopy Applied to Biomass Analysis for Application in the Field of Biofuels and Food Industry - O. Samek; A. Haroniková; N. Vaškovicová; K. Hrubanová; J Ježek; I. Márová; V. Krzyžánek; P. Zemánek (Microscopy and Microanalysis, 2015)
Keywords: MF

Three-Dimensional Optical Trapping of a Plasmonic Nanoparticle using Low Numerical Aperture Optical Tweezers - Oto Brzobohatý; M Šiler; J. Trojek; Lukáš Chvátal; Vítězslav Karásek; Aleš Paták; Zuzana Pokorná; Filip Mika; P. Zemánek (Sci. Rep., 2015)
Keywords: MF

Algal Biomass Analysis by Laser-Based Analytical Techniques—A Review - Pořízka, P.; P. Procházková; D. Procházka; Sládková, L.; Novotný, J.; Petrilak, M.; Brada, M.; O. Samek; Pilát, Z.; P. Zemánek; Adam, V.; Kizek, R.; et al. (Sensors, 2014)
Keywords: MF

Candida parapsilosis Biofilm Identification by Raman Spectroscopy - O. Samek; K. Mlynariková; Silva Bernatová; J Ježek; V. Krzyžánek; M Šiler; P. Zemánek; F. Růžička; V. Holá; M. Mahelová (Int. J. Mol. Sci., 2014)
Keywords: MF

Optical sorting of nonspherical and living microobjects in moving interference structures - P Jákl; Alejandro V. Arzola; M Šiler; Lukáš Chvátal; Karen Volke-Sepúlveda; P. Zemánek (Opt. Express, 2014)
Keywords: MF

Rotation, oscillation and hydrodynamic synchronization of optically trapped oblate spheroidal microparticles - Alejandro V. Arzola; P Jákl; Lukáš Chvátal; P. Zemánek (Opt. Express, 2014)
Keywords: MF

Experimental demonstration of optical transport, sorting and self-arrangement using a `tractor beam' - Oto Brzobohatý; Vítězslav Karásek; M Šiler; Lukáš Chvátal; Tomáš Čižmár; P. Zemánek (Nature Photon., 2013)
Keywords: MF

Following the mechanisms of bacteriostatic versus bacericidal action using Raman spectroscopy - Silva Bernatová; O. Samek; Z. Pilát; M. Šerý; J Ježek; P Jákl; M Šiler; V. Krzyžánek; P. Zemánek; V. Holá; M. Dvořáčková; F. Růžička (Molecules, 2013)
Keywords: MF

Holographic Raman tweezers controlled by hand gestures and voice commands - Z. Tomori; M. Antalík; P. Keša; J. Kaňka; P Jákl; M. Šerý; Silva Bernatová; P. Zemánek (Optics and Photonics Journal, 2013)
Keywords: MF

Metallic nanoparticles in a standing wave: optical force and heating - M Šiler; Lukáš Chvátal; P. Zemánek (J. Quant. Spectrosc. Radiat. Transf., 2013)
Keywords: MF

Optical forces in a non-diffracting vortex beam - M Šiler; P. Zemánek (J. Quant. Spectrosc. Radiat. Transf., 2013)
Keywords: MF

Optical manipulation of aerosol droplets using a holographic dual and single beam trap - Oto Brzobohatý; M Šiler; J Ježek; P Jákl; P. Zemánek (Opt. Lett., 2013)
Keywords: MF

Optical trapping of microalgae at 735–1064 nm: Photodamage assessment - Z. Pilát; J Ježek; M. Šerý; M. Trtílek; L. Nedbal; P. Zemánek (J. Photochem. Photobiol. B, 2013)
Keywords: MF

Spectral tuning of lasing emission from optofluidic droplet microlasers using optical stretching - Mehdi Aas; A. Jonáš; Alper Kiraz; Oto Brzobohatý; J Ježek; Z. Pilát; P. Zemánek (Opt. Express, 2013)
Keywords: MF

Application of laser-induced breakdown spectroscopy to the analysis of algal biomass for industrial biotechnology - P. Pořízka; D. Procházka; Z. Pilát; Krajčarová, L.; J. Kaiser; Malina, R.; J. Novotný; P. Zemánek; J Ježek; M. Šerý; Silva Bernatová; V. Krzyžánek; et al. (Spectrochim. Acta B, 2012)
Keywords: MF

Optical alignment and confinement of an ellipsoidal nanorod in optical tweezers: a theoretical study - J. Trojek; Lukáš Chvátal; P. Zemánek (J. Opt. Soc. Am. A, 2012)
Keywords: MF

Optical forces induced behavior of a particle in a non-diffracting vortex beam - M Šiler; P Jákl; Oto Brzobohatý; P. Zemánek (Opt. Express, 2012)
Keywords: MF

Raman microspectroscopy of algal lipid bodies: beta-carotene quantification - Z. Pilát; Silva Bernatová; J Ježek; M. Šerý; O. Samek; P. Zemánek; L. Nedbal; M. Trtílek (J. Appl. Phycol., 2012)
Keywords: MF

Speed enhancement of multi-particle chain in a traveling standing wave - M Šiler; Tomáš Čižmár; P. Zemánek (Appl. Phys. Lett., 2012)
Keywords: MF

Characterization of oil-producing microalgae using Raman spectroscopy - O. Samek; P. Zemánek; A. Jonáš; Telle, H. H. (Laser Phys. Lett., 2011)
Keywords: MF

Dynamic size tuning of multidimensional optically bound matter - Oto Brzobohatý; Vítězslav Karásek; Tomáš Čižmár; P. Zemánek (Appl. Phys. Lett., 2011)
Keywords: MF

The holographic optical micro-manipulation system based on counter-propagating beams - Tomáš Čižmár; Oto Brzobohatý; Kishan Dholakia; P. Zemánek (Laser Phys. Lett., 2011)
Keywords: MF

Parametric study of optical forces acting upon nanoparticles in a single, or a standing, evanescent wave - M Šiler; P. Zemánek (J. Opt., 2011)
Keywords: MF

Static and dynamic behavior of two optically bound microparticles in a standing wave - Oto Brzobohatý; Vítězslav Karásek; M Šiler; J. Trojek; P. Zemánek (Opt. Express, 2011)
Keywords: MF

Experimental and theoretical determination of optical binding forces - Oto Brzobohatý; Tomáš Čižmár; Vítězslav Karásek; M Šiler; Kishan Dholakia; P. Zemánek (Opt. Express, 2010)
Keywords: MF

Gripped by light: Optical binding - Kishan Dholakia; P. Zemánek (Rev. Mod. Phys., 2010)
Keywords: MF

Particle jumps between optical traps in a one-dimensional optical lattice - M Šiler; P. Zemánek (New. J. Phys., 2010)
Keywords: MF

Raman Microspectroscopy of Individual Algal Cells: Sensing Unsaturation of Storage Lipids in vivo - O. Samek; A. Jonáš; Z. Pilát; P. Zemánek; L. Nedbal; Tříska, J.; Kotas, P.; M. Trtílek (Sensors, 2010)
Keywords: MF

Extreme axial optical force in a standing wave achieved by optimized object shape - J. Trojek; Vítězslav Karásek; P. Zemánek (Opt. Express, 2009)
Keywords: MF

Longitudinal optical binding of several spherical particles studied by the coupled dipole method - Vítězslav Karásek; Oto Brzobohatý; P. Zemánek (J. Opt. A: Pure Appl. Opt., 2009)
Keywords: MF

High quality quasi-Bessel beam generated by round-tip axicon - Oto Brzobohatý; Tomáš Čižmár; P. Zemánek (Opt. Express, 2008)
Keywords: MF

Light at work: The use of optical forces for particle manipulation, sorting, and analysis. - A. Jonáš; P. Zemánek (Electophoresis, 2008)
Keywords: MF

Long-range one-dimensional longitudinal optical binding - Vítězslav Karásek; Tomáš Čižmár; Oto Brzobohatý; P. Zemánek; V. Garcés-Chávez; Kishan Dholakia (Phys. Rev. Lett., 2008)
Keywords: MF

Static optical sorting in a laser interference field - P Jákl; Tomáš Čižmár; M. Šerý; P. Zemánek (Appl. Phys. Lett., 2008)
Keywords: MF

Surface delivery of a single nanoparticle under moving evanescent standing-wave illumination - M Šiler; Tomáš Čižmár; A. Jonáš; P. Zemánek (New. J. Phys., 2008)
Keywords: MF

Analytical description of longitudinal optical binding of two spherical nanoparticles - Vítězslav Karásek; P. Zemánek (J. Opt. A: Pure Appl. Opt., 2007)
Keywords: MF

Axial optical trap stiffness influenced by retro-reflected beam - P Jákl; M. Šerý; J Ježek; M. Liška; P. Zemánek (J. Opt. A: Pure Appl. Opt., 2007)
Keywords: MF

Cellular and colloidal separation using optical forces - Kishan Dholakia; MacDonald, M. P.; P. Zemánek; Tomáš Čižmár (Methods in Cell Biology, 2007)
Keywords: MF

Optical forces acting on a nanoparticle placed into an interference evanescent field - M Šiler; P. Zemánek (Opt. Commun., 2007)
Keywords: MF

Optical tracking of spherical micro-objects in spatially periodic interference fields - Tomáš Čižmár; P. Zemánek (Opt. Express, 2007)
Keywords: MF

Opto-fluidic micromanipulation system based on integrated polymer waveguides - P Jákl; M. Šerý; J Ježek; P. Zemánek; Ormos, P.; Valkai, S.; Kelemen, L. (J. Optoel Adv. Mater., 2007)
Keywords: MF

Transverse particle dynamics in a Bessel beam - Milne, Graham; Kishan Dholakia; McGloin, David; Karen Volke-Sepúlveda; P. Zemánek (Opt. Express, 2007)
Keywords: MF

Analysis of optical binding in one dimension - Vítězslav Karásek; Kishan Dholakia; P. Zemánek (Appl. Phys. B, 2006)
Keywords: MF

Formation of long and thin polymer fiber using nondiffracting beam - J Ježek; Tomáš Čižmár; V. Neděla; P. Zemánek (Opt. Express, 2006)
Keywords: MF

Optical forces generated by evanescent standing waves and their usage for sub-micron particle delivery - M Šiler; Tomáš Čižmár; M. Šerý; P. Zemánek (Appl. Phys. B, 2006)
Keywords: MF

An optical nanotrap array movable over a milimetre range - Tomáš Čižmár; M Šiler; P. Zemánek (Appl. Phys. B, 2006)
Keywords: MF

Optical sorting and detection of sub-micron objects in a motional standing wave - Tomáš Čižmár; M Šiler; M. Šerý; P. Zemánek; V. Garcés-Chávez; Kishan Dholakia (Phys. Rev. B, 2006)
Keywords: MF

Sub-micron particle organization by self-imaging of non-diffracting beams - Tomáš Čižmár; V. Kollárová; Zdeněk Bouchal; P. Zemánek (New. J. Phys., 2006)
Keywords: MF

Optical conveyor belt for delivery of submicron objects - Tomáš Čižmár; V. Garcés-Chávez; Kishan Dholakia; P. Zemánek (Appl. Phys. Lett., 2005)
Keywords: MF

Two-and three-beam interferometric optical tweezers - A. Casaburi; G. Pesce; P. Zemánek; A. Sasso (Opt. Commun., 2005)
Keywords: MF

Optical forces acting on Rayleigh particle placed into interference field - P. Zemánek; Vítězslav Karásek; A. Sasso (Opt. Commun., 2004)
Keywords: MF

Behaviour of an optically trapped probe approaching a dielectric interface - P Jákl; M. Šerý; J Ježek; A. Jonáš; M. Liška; P. Zemánek (J Mod. Optics, 2003)
Keywords: MF

Theoretical comparison of optical traps created by standing wave and single beam - P. Zemánek; A. Jonáš; P Jákl; M. Šerý; J Ježek; M. Liška (Opt. Commun., 2003)
Keywords: MF

Simplified description of optical forces acting on a nanoparticle in the Gaussian standing wave - P. Zemánek; A. Jonáš; M. Liška (J. Opt. Soc. Am. A, 2002)
Keywords: MF

Single beam trapping in front of reflective surfaces - A. Jonáš; P. Zemánek; E. - L. Florin (Opt. Lett., 2001)
Keywords: MF

Optical trapping of nanoparticles and microparticles using Gaussian standing wave. - P. Zemánek; A. Jonáš; L. Šrámek; M. Liška (Opt. Lett., 1999)
Keywords: MF

Atomic dipole trap formed by a blue detuned strong Gaussian standing wave - P. Zemánek; C. J. Foot (Opt. Commun., 1998)
Keywords: MF

Optical trapping of Rayleigh particles using a Gaussian standing wave - P. Zemánek; A. Jonáš; L. Šrámek; M. Liška (Opt. Commun., 1998)
Keywords: MF